STRATEGI GURU MEMINIMALISIR KEJENUHAN DALAM SUASANA BELAJAR PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 3 TEBING TINGGI KOTA SELATPANJANG - Jamila Khairina; Muhiddinur Kamal; Iswantir M; Wedra Aprison (KOLONI, 2022)
This research is motivated by boredom in the learning atmosphere experienced by students so that it becomes a problem that comes suddenly unexpectedly and is desired in the learning process, so that it becomes something that hinders the goal of achieving education in Indonesia. The boredom of learning causes students to not be able to capture and take the essence of the lessons taught by teachers at SMP Negeri 3 Tebing Tinggi, Selatpanjang City. This study aims to determine what strategies are used by teachers and what factors influence the strategies of Islamic religious education teachers in minimizing learning saturation at SMP Negeri 3 Tebing Tinggi, Selatpanjang City. This type of research is field research, namely research with a qualitative approach. The subjects in this study were educators and class VIII students at SMP Negeri 3 Tebing Tinggi, Selatpanjang City, the object of this research is the factors that influence learning saturation and teacher strategies to minimize boredom in the learning atmosphere at SMP Negeri 3 Tebing Tinggi, Selatpanjang City. Data collection techniques in this study are interviews, observation and documentation. For data analysis, the writer uses qualitative analysis by describing actual events in the form of sentences and then drawing conclusions. Based on the research, it was stated that the teacher's strategy was to minimize boredom in the learning atmosphere of Islamic religious education at SMPN 3 Tebing Tinggi, Selatpanjang City using various strategies including, Approaching students, Applying Varied Learning Methods, Ice Breaking and Entering funny things during learning. , Creating a conducive and fun environment as well as giving gifts and motivation to students. The causes of student saturation are the learning environment does not provide support, perfunctory learning strategies, are often given excessive exercises and memorization assignments and the way teachers teach does not vary. Islamic religious education teachers at SMP Negeri 3 Tebing Tinggi, Selatpanjang City, have been very good at minimizing learning saturation, both in terms of strategies and supporting factors in minimizing learning boredom.  Keywords: Teacher Strategy, Saturation, Learning Atmosphere, Islamic Religious Education.